Children and teens moving towards mental health - Pires, Sara (2021)
Childhood and adolescence are periods of rapid growth when several structural and behavioral transformations take place. It is important to identify positive environmental exposures during these years and establish behavioral patterns that may have a positive effect on the development of these populations. There is an increasing body of evidence showing that regular exercise has unquestionable physical, social, and psychological benefits, contributing to general health and wellbeing. The aim of this study was to review the available literature regarding the impact of regular physical activity on the mental health of children and adolescents and to highlight possible mechanisms involved in this association. Study findings suggest that there is a global positive impact of physical activity on mental health, with the strongest effect related to the decrease of depressive symptoms. Other benefits include improvement in self-esteem, cognitive function, and sleep quality and a reduction of externalizing behaviors and anxiety symptoms. Competitive and esthetical sports were an exception. Overall, the current evidence allows recommending regular physical activity in children and adolescents, not only for its organic but also mental health benefits.